Development Milk Ice-cream Supplemented of Chicken Breast - Kitjavorasatien, Suthida; Pomyen, Vorathon; Pomnoi, Woralak (RMUTP Research Journal Sciences and Technology, 2021)
Milk ice cream is the one of most popular dessert in many countries. But the most milk ice cream contains high amounts of sugar and fat. It is for this reason that consumers who exercise regularly concern about the impact of ice cream consumption on health and have led to a considerable rise in high protein ice cream demand for this consumer group. Therefore, the objective of this study was to develop the milk ice cream with high protein from chicken breast by varying chicken breast in milk ice cream at 5, 10 and 15% by total weight. The result showed that 10 % chicken breast ice cream had the best physical and sensory properties. The viscosity, overrun, texture and melting rate of the developed formula were 89.05 cps, 108.05%, 34,584 g force and 23%, respectively. The lightness (L*), redness (a*) and yellowness (b*) value were 87.10, 5.08 and 20.54 respectively.